Niche Konselor di Indonesia dalam Pendidikan Formal - Gumilang, Galang Surya (JURNAL FOKUS KONSELING, 2017)
Abstract: This article describes and discusses (1) understanding of "niche", (2) niche counselor in Indonesia, (3) niche counselor on formal education, (4) niche counselor "to come" in Indonesia. Constraints to realize the role of school counselors, among others, principals and subject teachers who do not understand the function of guidance and counseling. Many school counselors who are not graduates of Guidance and Counseling but are merely odd or functional. Many and almost average in school School counselors do not have adequate facilities to work ideally, so the counselors performance is less than optimal. School counselors are not considered important by students and educational components in schools. To overcome these obstacles required the participation of both governments, ABKIN, own counselor, and community environment, especially the school environment. From the counselor and the institution that shelter it needs to show good performance and from other components need to give trust and opportunity to the counselor to show its performance.Keywords: Niche, Counselor, Formal Education